Contracting by small farmers in commodities with export potential: Assessing farm profits of lentil growers in Nepal - Kumar, Anjani; Roy, Devesh; Tripathi, Gaurav; Joshi, Pramod Kumar; Adhikari, Rajendra Prasad (International Food Policy Research Institute, 2016)
This study is undertaken to quantify the benefits of contract farming (CF) on farmers’ income in a case where new market opportunities are emerging for smallholder farmers in Nepal. CF is emerging as an important form of vertical coordination in the agrifood supply chain. The prospect for CF in a country like Nepal with accessibility issues, underdeveloped markets, and a lack of amenities remains ambiguous. Contractors find it difficult to build links in these cases, particularly when final consumers have quality and safety requirements. However, a lack of other market opportunities makes the contracts more sustainable. The latter happens if there are product-specific quality advantages because of agroecology and, more important, lack of side-selling opportunities. Concerns remain about monoposonistic powers of the buyers when small farmers do not have outside options. Results of this study show that CF is significantly more profitable (81 percent greater net income) than independent production, the main pathway being higher yield and price realization. The positive impact of CF on farmers’ profits can help Nepal in harnessing the growing demand for pulses, especially in neighboring international markets, like India.